Model Pengembangan Wisata Halal Berbasis Masjid di Provinsi Aceh - Abrar - Amri; Muhammad Yasir Yusuf; Hafiizh Maulana (ITB AAS INDONESIA Surakarta, 2022)
Abstract The economic development of the mosque can be a source of new economic growth by optimizing the potential of the existing mosque congregation. This study has urgency in order to build a conceptual framework for a mosque-based business development model. This study uses an expert system approach in designing an economic development model within the framework of enforcing Islamic Sharia in Aceh and encouraging community economic growth (Jamaah). The research was conducted at several mosques in Aceh. The technique of collecting data and information is collected by formulating a model design through observation, documentation, and distributing questionnaires to the management of the Mosque Prosperity Agency (BKM) and jamaah. Based on the results of the study, the development of a mosque-based economy in has considerable potential. This potential can be seen from the start of a more modern mosque management and the positive response to the idea of developing the mosque's economy from the administrators of the mosque's prosperity agency and jamaah. The results of the study recommend that mosques must prepare Human Resources for managing autonomous business units by establishing a Sharia Financial Institution.